2005
DOI: 10.1136/bjsm.2004.016675
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for secular trends in children’s physical activity behaviour

Abstract: It is not clear whether the global increase in weight problems in children is the result of excessive energy intake or decreasing energy expenditure. Methodological limitations have made it difficult to analyse. There is evidence that at least part of the problem may lie with increasing energy consumption, but it is important to examine the other side of the energy equation also. However, it is not possible to conclusively describe physical activity trends because of the absence of suitable baseline data. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
244
2
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(274 citation statements)
references
References 43 publications
9
244
2
11
Order By: Relevance
“…One 5-year longitudinal study of physical activity and sedentary behaviour during adolescence reported substantial reductions in moderate to vigorous physical activity (MVPA), particularly among girls, and increasing leisure-time computer use in girls and boys (36) . A 2005 review of evidence on sedentariness, fitness and attitudes concluded that physical activity in clearly defined contexts, active transport, school physical education and organised sports was declining in many countries (37) . In a study involving two 10-year-separated cross-sectional cohorts of Czech adolescents in 2000 and 2010 the doubling in obesity was accompanied by an increase in total sedentary behaviour, especially in girls, and a switch from TV watching to computer games (38) .…”
Section: Drivers Of Obesity: the Current Gluttony V Sloth Debatementioning
confidence: 99%
“…One 5-year longitudinal study of physical activity and sedentary behaviour during adolescence reported substantial reductions in moderate to vigorous physical activity (MVPA), particularly among girls, and increasing leisure-time computer use in girls and boys (36) . A 2005 review of evidence on sedentariness, fitness and attitudes concluded that physical activity in clearly defined contexts, active transport, school physical education and organised sports was declining in many countries (37) . In a study involving two 10-year-separated cross-sectional cohorts of Czech adolescents in 2000 and 2010 the doubling in obesity was accompanied by an increase in total sedentary behaviour, especially in girls, and a switch from TV watching to computer games (38) .…”
Section: Drivers Of Obesity: the Current Gluttony V Sloth Debatementioning
confidence: 99%
“…The literature on this issue however in not entirely consistent: Several authors reported an increase of indoor activities such as watching television and playing computer 80 games and decreasing outdoor activities like walking or biking to school or organized sports (Dollman et al 2005;Ham et al 2008;Hofferth 2009). In contrast, other studies observed an increase in children's organized activities while sedentary activities like watching television have decreased (Sturm 2005).…”
mentioning
confidence: 99%
“…Clearly, our present systems are failing and have been doing so for some time 6 . Successive generations of Australian school children have lost their free play and other opportunities to be active have been eroded from daily life 41 . Replacing this lost opportunity will not be easy.…”
Section: Resultsmentioning
confidence: 99%